LITERATURE REVIEW: POTENSI OBAT BAHAN ALAM DARI TANAMAN SEMANGGI AIR (Marsilea crenata) - Chandra, Pra Panca Bayu; Laksmitawati, Dian Ratih (Jurnal Buana Farma, 2025)
The use of plants as natural medicine is used because Indonesia has a wealth of natural resources. One of the plants used is water clover (Marsilea crenata). This plant is used as food and medicine. This study aims to identify the potential of natural medicine from water clover (Marsilea crenata). The research method in the literature study is to apply journal searches to the Google Scholar, Science Direct, and Pubmed databases with the keywords water clover (Marsilea crenata) and pharmacological activity. The journals used are national and international journals published from 2012 to 2025. The journals used are research on the potential of water clover as a natural medicine in silico, in vitro and in vivo. From the results of the literature study, 9 journals were obtained. After obtaining research data from journals, they were then combined and studied, then explained and explained systematically. The results of the study showed that water clover leaves in both extract and fraction forms have pharmacological activities including anticholesterolemia, antihyperglycemia, antioxidant, anti-inflammatory, HMG-CoA reductase enzyme inhibitory activity, sperm quality improvement activity in hyperglycemic mice, anti-neuroinflammatory serum. The content of secondary metabolites found in Marsilea crenata is a bioactive compound that is responsible for providing pharmacological activity.